Cover Picture: Reconstitution of Biosynthetic Machinery for the Synthesis of the Highly Elaborated Indole Diterpene Penitrem (Angew. Chem. Int. Ed. 19/2015). Issue 19 (8th April 2015) - Liu, Chengwei; Tagami, Koichi; Minami, Atsushi; Matsumoto, Tomoyuki; Frisvad, Jens Christian; Suzuki, Hideyuki; Ishikawa, Jun; Gomi, Katsuya; Oikawa, Hideaki
<x xml:space="preserve">Abstract</x> The biosynthetic gene cluster of the highly complex indole diterpene penitrem is identified by H. Oikawa et al. in their Communication on page 5748 ff. Thirteen out of the seventeen involved transformations were elucidated by heterologous reconstitution of the relevant genes in Aspergillus oryzae and found to involve a prenylation‐initiated cationic cyclization and two successive P450‐catalyzed oxidative transformations for the installation of the characteristic bicyclo[4.2.0]octane skeleton.